Introduction: Work and Organizing in Scientific and Technological Phenomena - Bruni, Attila (Tecnoscienza – Italian Journal of Science & Technology Studies, 2024)
Work and organizing have always been central to Science and Technology Studies (STS). Focusing on work and organizing practices has allowed STS to highlight the routine activities of scientists and the often-invisible work embedded in scientific and technological phenomena. STS have been one of the major sources of inspiration for developing a non-deterministic view of technology in Organization Studies (OS), but contemporary STS seem to have forgotten part of their interest towards work and organization, as from the scarcity of these themes in major STS conference tracks and special journal issues over the past fifteen years. This special issue aims to reinvigorate the focus on work and organization within STS, suggesting that insights from OS can enrich STS frameworks. The introduction proposes five propositions about work and organizing in science and technology, setting the stage for the issue’s contributions.